2013
DOI: 10.9734/bjmmr/2013/3453
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of Fullerene Derivatives in PDT and Radiotherapy of Cancers

Abstract: Nanoparticles of fullerenes and their water-soluble derivatives have been firmly introduced into solution of medical problems. Although there are still debates about their toxicity and long-term consequences of their application in the clinic, the success of fullerenes application in some sections is undeniable, in particular, in photodynamic therapy (PDT) of cancer tumors. Besides there are interesting data on radiotherapy where fullerenes appear to be more transporters than drugs, but due to own cytoprotecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 108 publications
(118 reference statements)
0
9
0
1
Order By: Relevance
“…Comparing phototoxicity toward HaCaT of ( -CyD) 2 /C 60 (c-cyclodextrin bicapped C 60 ) and fullerenol, Zhao et al concluded that fullerenol was less phototoxic [68]. The aggregation of fullerenol in aqueous solution results in a loss of its intrinsic photochemical reactivity with respect to the production of superoxide and singlet oxygen [69,70]. The free radical (type I) mechanisms are considered to be involved in fullerenol phototoxicity.…”
Section: Journal Of Nanomaterialsmentioning
confidence: 99%
“…Comparing phototoxicity toward HaCaT of ( -CyD) 2 /C 60 (c-cyclodextrin bicapped C 60 ) and fullerenol, Zhao et al concluded that fullerenol was less phototoxic [68]. The aggregation of fullerenol in aqueous solution results in a loss of its intrinsic photochemical reactivity with respect to the production of superoxide and singlet oxygen [69,70]. The free radical (type I) mechanisms are considered to be involved in fullerenol phototoxicity.…”
Section: Journal Of Nanomaterialsmentioning
confidence: 99%
“…Fullerenes are very efficacious generators of singlet oxygen with a quantum yield of 1 O 2 close to one. They absorb light efficiently in the ultraviolet and moderately in the visible regions of the spectrum [14], which paves the way for their application in photodynamic therapy [15].…”
Section: Introductionmentioning
confidence: 99%
“…The enhanced efficiency of Dox included in nanoplatforms together with such photosenitizers as chlorin 6 [11,13,14], phthalocyanines [12,15,21], indocyanine green [22], merocyanine [9], methylene blue [10], and perfluorocarbon [16] was recently reported. The carbon nanostructure C 60 fullerene [23] (here abbreviated consistently C 60 ) has attracted attention as a photosensitizer [1,24,25,26,27] due to its unique physicochemical behavior, high quantum yield of ROS production [28], photostability, low photobleaching [25] as well as predominant mitochondrial localization [29,30,31,32]. Pristine C 60 stable colloid solution with a negligible toxicity against normal cells [33,34] was explored for PDT [26,28,31,35,36,37,38].…”
Section: Introductionmentioning
confidence: 99%
“…The carbon nanostructure C 60 fullerene [23] (here abbreviated consistently C 60 ) has attracted attention as a photosensitizer [1,24,25,26,27] due to its unique physicochemical behavior, high quantum yield of ROS production [28], photostability, low photobleaching [25] as well as predominant mitochondrial localization [29,30,31,32]. Pristine C 60 stable colloid solution with a negligible toxicity against normal cells [33,34] was explored for PDT [26,28,31,35,36,37,38]. A pronounced pro-apoptotic effect was detected in leukemic cells treated with pristine ≤20 µM C 60 and irradiated with UV-Vis light in the range of 320 – 600 nm [26,35,36,37,39,40].…”
Section: Introductionmentioning
confidence: 99%